'Maybe I Shouldn't Talk': The Role of Power in the Telling of Mental Health Recovery Stories. (October 2022) - Llewellyn-Beardsley, Joy; Rennick-Egglestone, Stefan; Pollock, Kristian; Ali, Yasmin; Watson, Emma; Franklin, Donna; Yeo, Caroline; Ng, Fiona; McGranahan, Rose; Slade, Mike; Edgley, Alison
Mental health 'recovery narratives' are increasingly used within teaching, learning and practice environments. The mainstreaming of their use has been critiqued by scholars and activists as a co-option of lived experience for organisational purposes. But how people report their experiences of telling their stories has not been investigated at scale. We present accounts from 71 people with lived experience of multiple inequalities of telling their stories in formal and informal settings. A reflexive thematic analysis was conducted within a critical constructivist approach. Our overarching finding was that questions of power were central to all accounts. Four themes were identified: (1) Challenging the status quo; (2) Risky consequences; (3) Producing 'acceptable' stories; (4) Untellable stories. We discuss how the concept of narrative power foregrounds inequalities in settings within which recovery stories are invited and co-constructed, and conclude that power imbalances complicate the seemingly benign act of telling stories of lived experience.